Expression

\(a + ib = \dfrac{(x+i)^2}{2x^2+1}\)

= \( \dfrac{x^2+i^2+2xi}{2x^2+1}\)

= \( \dfrac{x^2-1+i2x}{2x^2+1}\)

= \( \dfrac{x^2-1}{2x^2+1}+i (\dfrac{2x}{2x^2+1})\)

On comparing

\( a^2+b^2= \dfrac{(x^2+1)^2}{(2x^2+1)^2}+(\dfrac{2x}{2x^2+1})^2\)

= \( \dfrac{x^4+1-2x^2+4x^2}{(2x+1)^2}\)

= \( \dfrac{x^4+1+2x^2}{(2x^2+1)^2}\)

= \( \dfrac{(x^2+1)^2}{(2x^2+1)^2}\)

\( a + ib = \dfrac{(x^2+1)^2}{(2x^2+1)^2}\)

Hence, proved

Answered by Abhisek | 1 year agoShow that 1 + i^{10} + i^{20} + i^{30} is a real number?

Solve the quadratic equations by factorization method only 6x^{2} – 17ix – 12 = 0

Solve the quadratic equations by factorization method only x^{2} + (1 – 2i)x – 2i = 0

Solve the quadratic equations by factorization method only x^{2} + 10ix – 21 = 0

Solve the quadratic equations by factorization method only 17x^{2} – 8x + 1 = 0